JOB SATISFACTION AMONG THE EMPLOYEES IN NOVI SADS TOURIST AGENCIES - Kovačević, Bojana; Gajić, Tamara; Penić, Mirjana (Economics of Agriculture, 2012)
This paper deals with current issues in the tourism sector, which is employee satisfaction, and result in the synthesis of theory and research findings on employee satisfaction in travel agencies, a factor for success and achieve greater profitability and competitiveness. The primary goal of this study was to determine the extent of employee satisfaction among staff in Novi Sads tourist agencies, as well as to determine the parameters of employee motivation and enable the possible influence on bigger productivity and business competitiveness. The main objective of this study was to confirm a specific hypothesis. In this paper, the main hypothesis is that generally observing, staff employed in Novi Sads travel agencies are mainly pleased with all offered segment or determinants that affect their business and it was confirmed. The basic method in this study is to survey a random sample, and analysis of results obtained from the data collected. Data processing used the SPSS program, version 17.0. Included were 107 respondents and the outcome reached by applying or use of statistical methods and secondary publications, confirming certain hypotheses that have been posted in the paper. Analyzing and processing the survey, which completely had a research character, led to the concrete and practical conclusions, proposals and guidelines about job satisfaction in tourist agencies in Novi Sad.